Improved phrase search construction over encrypted data in cloud storage. (2017) - Kong, Fanyu; Wang, Jie; Yu, Jia; Wang, Xu An
Searchable encryption schemes are important security techniques for guaranteeing cloud customers' data privacy in cloud storage outsourcing service. Kissel proposed a verifiable single-phase phrase search scheme using symmetric encryption algorithms, which was proved non-adaptively secure in the semi-honest-but-curious (SHBC) model. We present a security analysis of Kissel's scheme and show that the cloud service provider can obtain some new phrases' trapdoors and search outcomes based on the client's a phrase query. We propose an improvement to simplify Kissel's scheme and enhance its security. Finally, we give a security analysis and efficiency analysis of the improved phrase search scheme on encrypted data. The analysis shows that our improved scheme is proved non-adaptively secure and has better efficiency.